2012
DOI: 10.1134/s2079059712010108
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of the rye 2R chromosome in backcrosses of wheat-rye 2R(2D) substitution lines to common wheat varieties

Abstract: Transmission of the rye 2R chromosome in backcrosses of wheat-rye substitution lines 2R(2D) 1 , 2R(2D) 2 , and2R(2D) 3 (Triticum aestivum L. cv. Saratovskaya 29 / Secale cereale L. cv. Onokhoiskaya, 2n = 42) to common wheat varieties Saratovskaya 29 (S29), Novosibirskaya 67 (N67), and line Lutescens 307/97 23 (Lut307) has been studied. Rye chromosomes are present in the progeny of hybridsLut307 × 2R(2D) 1 in the disomic or monosomic states; telocentrics and 2R/2D translocations have been recorded as well. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Studies of the meiotic behaviour of 2D and 2R in dimonosomic lines of wheat showed no pairing between them (Silkova et al 2014). The only T2R.2DL translocations found thus far have resulted from ruptures in the centromeric region, which were followed by centric fusion; thus, these events did not involve small chromosome segments (Krasilova et al 2012).…”
Section: Introductionmentioning
confidence: 92%
“…Studies of the meiotic behaviour of 2D and 2R in dimonosomic lines of wheat showed no pairing between them (Silkova et al 2014). The only T2R.2DL translocations found thus far have resulted from ruptures in the centromeric region, which were followed by centric fusion; thus, these events did not involve small chromosome segments (Krasilova et al 2012).…”
Section: Introductionmentioning
confidence: 92%
“…To date, the reasons for the elimination of donor chromosomes in backcross hybrids remain unclear; however, it is known that in wheat-rye lines, the frequency of introgression of an alien chromosome depends both on the genotype of the line and on the genotype of the variety used in the crossing (Krasilova et al, 2011). Analysis of introgression lines of hybrid wheat with Aegilops columnaris Zhuk.…”
mentioning
confidence: 99%